Increasing the competency of Sultan Ageng Tirtayasa University PVTE Students Through PLC Outseal Training - Bagus Dwi Cahyono; Irwanto Irwanto (Yayasan Adra Karima Hubbi, 2024)
Background. Outseal PLC Training for PVTE Students at Sultan Ageng University Programmable Logic Controller is a device that can be programmed according to industrial process needs. Purpose. This activity is a service activity for PVTE Study Program lecturers at Sultan Ageng Tirtayasa University which is expected to be able to improve students' skills in terms of being equipped for the world of work. Method. This activity is a service activity for PVTE Study Program lecturers at Sultan Ageng Tirtayasa University which is expected to be able to improve students' skills in terms of being equipped for the world of work. This PLC Outseal Training activity is carried out face to face for 8 hours in the FKIP educational room at Sultan Ageng Tirtayasa University. This training method uses a practical based method. Results. The evaluation results show that students seem interested and do not experience problems when practicing PLC. Conclusion. This training has a significant impact on students' skills in industrial automation concentration courses.